Dynamic control of a fixed pattern rectifier. - Ghijselen, J.A.L (IEEE Transactions on power electronics)
A three-phase, sinusoidal, active rectifier is presented, based on the classical inverter topology. The switches are governed by a fixed pulse width modulation (PWM) pattern, and the control strategy is extremely simplified as compared with many active rectifiers. General equations describing the steady-state operation of fixed pattern rectifiers are given. A dynamic model of the simplified control rectifier is presented, based on the nonlinear equations describing the system. Based on the analytical model, the classical PI-controller yields poor dynamic results, especially at low load conditions. However, the dynamic performance of the prototype is much better, due to the effects of commutation dead time of the rectifier switches. It is shown that a small modification to the classical PI-controller yields a remarkable increase in amplitude and phase margin, without slowing down the response. The obtained dynamics show a clear improvement over the classical PI-controller and are adequate for most applications